(3eSFhdjI GdSeSGQ Yf EJeGe GdYedjGJ GdMGVQI ddHhQUI (B: s (3OQGSI ebGQfI Hjf GdbGfhf GdJLGQj hGdabg GdESdGej (B/ s - (3eMeO aQGL YeQ GdeGRfjs; (3CfhQ eMehO OHhQ (B: s; (3SGej YHOGdHGbj CHhUGdM (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B-(3LGeYI GdbGgQI,s, 2011)
(3JJfGhd GdQSGdI ehVhY eSFhdjI GdSeSGQ Yf EJeGe GdYedjGJ GdMGVQI ddHhQUI; MjK HOCJ HaUd JegjOj Yf HhQUI GdChQGb GdeGdjI ef MjK GdJYQja HGdHhQUI, hJGQjN fTCI GdHhQUGJ, heQGMd JWhQgG, Ke GdHGH GdChd djJfGhd TQcGJ GdSeSQI GdYGedI aj fTGW JOGhd GdChQGb GdeGdjI aj GdbGfhf hGdabg GdESdGej, hCNjQG GdHGH GdKGfj Yf YedjGJ GdHhQUI heSFhdjI GdSeSGQ Yf EJeGegG(B.s
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B2011.s
(3HHdjhLQGajG(B: (3UaMGJ(B645-680.s
Keywords: (3HhQUI GdChQGb GdeGdjIs; (3bGfhf Shb QCS GdeGds; (3JOGhd GdChQGb GdeGdjIs; (3TQcGJ GdSeSQIs; (3YbO GdSeSQIs; (3SeSGQ GdChQGb GdeGdjIs; (3YedjGJ GdHhQUIs; (3YedjGJ GdHhQUI GdMGVQI hGdBLdIs; (3GdChQGb GdeGdjIs; (3GdCSge s; (3GdSfOGJs; (3MUU GdJCSjS Ch GdCQHGMs; (3Uchc GdJehjds; (3hKGFb GdGSJKeGQs; (3eSFhdjI TQcGJ GdSeSQI aj GdChQGb GdeGdjIs; (3GdeSFhdjI GdeOfjI dTQcGJ GdSeSQIs; (3GdeSFhdjI GdYbOjI dTQcGJ GdSeSQIs; (3GdeSFhdjI GdLfGFjI dTQcGJ GdSeSQIs; (3GdeSFhdjI GdJCOjHjI dTQcGJ GdSeSQIs; (3TQcGJ GdSeSQI aj Gdabg GdESdGejs; (3HhQUI GdChQGb GdeGdjI aj Gdabg GdESdGejs; (3YedjGJ GdHhQUI aj Gdabg GdESdGejs; (3YbO GdSeSQI aj Gdabg GdESdGejs; (3Shb GdChQGb GdeGdjI aj GdTQjYI GdESdGejIs; (3HhQUI GdChQGb GdeGdjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- 2011